Effects of facts devices on static voltage stability - Moghavvemi, M.; Faruque, M.O. (2000)
This paper presents a study of FACTS devices mainly Static Var Compensator (SVC) and Controlled series compensator (CSC). Their steady-state modeling and effects on power system performance have been studied. It also studies static stability improvement of power system and hence power flow improvement in the network. Standard stability evaluation technique has been used to identify the optimum place for the implementation of Flexible AC Transmission System (FACTS) devices and the effects of FACTS on system loadability has been studied and presented here. The technique to identify the optimum location for the placement of FACTS devices is based on the concept of maximum power transferring capability of the lines and buses. The study has been carried out on the IEEE 24 and 118 Bus Test Systems. Study reveals that incorporation of FACTS devices significantly enhanced system stability as well as power transfer capability of the system.